The Role of Brand Trust Mediating the Influence of Electronic Word of Mouth on Erigo Fashion Purchase Decisions in Denpasar City - Chandra, Wayan Haris; Suasana, I Gst. A. Kt. Gd.; Sukawati, Tjokorda Gde Raka; Artini, Luh Gede Sri (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to ascertain how brand trust functions as a mediator between Electronic Word of Mouth (E-WOM) and Erigo fashion product purchases in Denpasar City. The existence of Erigo stores in Bali, which are limited to Denpasar, served as the basis for the choice of location. One hundred Erigo customers participated in the non-probability sampling technique. Questionnaires were used to gather data, and the Sobel test and path analysis were used for analysis. The findings demonstrated that the impact of E-WOM on purchase decisions could be mediated by brand trust. By paying attention to E-WOM and brand trust, these findings should help Erigo make better purchasing decisions.